A multinational health professional perspective of the prevalence of mood disorders in patients with acute and chronic wounds - Upton, Dominic (Int Wound J, 2013)
Recent research has started to identify mood disorders and problems associated with acute and chronic wounds, which have been shown to contribute to delayed healing, poor patient well‐being and a reduced quality of life. Furthermore, mood disorders have been shown to have a negative impact on financial costs for service providers and the wider society in terms of treatment and sickness absence. This study aimed to survey a multinational sample of health professionals to explore their perspective and awareness of mood disorders amongst acute and chronic wound patients. Responses were received from n = 908 health professionals working in Asia, Africa, Australia, Europe, North America and South America. A strong awareness of the prevalence of mood disorders appeared to be widespread among the health professionals across the world, in addition to a view on the potential factors contributing to these problems with mood. Despite this, it was thought that few patients were actually receiving treatment for their mood disorders. Implications for clinical practice include the need for health professionals to engage actively with their patients to enable them to learn from their experiences. Studies that explore the benefits of treatments and techniques appropriate for minimising mood disorders in patients with wounds would provide empirical evidence for health professionals to make recommendations for patients with acute and chronic wounds.